2021
DOI: 10.1038/s41598-020-79621-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a predominant genotype of Mycobacterium tuberculosis in Brazilian indigenous population

Abstract: After nearly a century of vaccination and six decades of drug therapy, tuberculosis (TB) kills more people annually than any other infectious disease. Substantial challenges to disease eradication remain among vulnerable and underserved populations. The Guarani-Kaiowá people are an indigenous population in Paraguay and the Brazilian state of Mato Grosso do Sul. This community, marginalized in Brazilian society, experiences severe poverty. Like other South American indigenous populations, their TB prevalence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…The Latino-American family (Lineage 4.3) has been observed to predominate in South America ( Brynildsrud et al., 2018 ). Interestingly in a recent study using samples from the Guarani-Kaiowaí indigenous people living in Paraguay and the Brazilian state of Mato Grosso do Sul, Hadi et al. (2021) found that 81% of the isolates belong to sub-lineage 4.3.3, followed by 4.3.4.2 (13%), in a similar way to our findings ( Hadi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The Latino-American family (Lineage 4.3) has been observed to predominate in South America ( Brynildsrud et al., 2018 ). Interestingly in a recent study using samples from the Guarani-Kaiowaí indigenous people living in Paraguay and the Brazilian state of Mato Grosso do Sul, Hadi et al. (2021) found that 81% of the isolates belong to sub-lineage 4.3.3, followed by 4.3.4.2 (13%), in a similar way to our findings ( Hadi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In both cases, Amerindian people were the hosts, which makes possible the adaptation of these sub-lineages to people with this genetic background, as has been seen in Tanzania where L3.1.1 is highly successful in Dar es Salam ( Zweyer et al., 2021 ). The comparison of our 4.3.3 genomes with those from Hadi et al.’s (2021) study resulted in the formation of a separated cluster with two Amazonian isolates in the group, which strengthen the possible relationship with South American isolates. These Chiapas’ 4.3.3 isolates, even if they were not identical, showed a similar pattern in mutations in genes associated with antimicrobial resistance.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations